2021
DOI: 10.3389/fmicb.2021.754306
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Engineering of Enterobacter aerogenes for Improved 2,3-Butanediol Production by Manipulating NADH Levels and Overexpressing the Small RNA RyhB

Abstract: Biotechnological production of 2,3-butanediol (2,3-BD), a versatile platform bio-chemical and a potential biofuel, is limited due to by-product toxicity. In this study, we aimed to redirect the metabolic flux toward 2,3-BD in Enterobacter aerogenes (E. aerogenes) by increasing the intracellular NADH pool. Increasing the NADH/NAD+ ratio by knocking out the NADH dehydrogenase genes (nuoC/nuoD) enhanced 2,3-BD production by up to 67% compared with wild-type E. aerogenes. When lactate dehydrogenase (ldh) was knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…However, less research has been done in recent years to limit the succinate production (Thapa et al 2019 ). Instead, most studies have focused on limiting lactate (Ge et al 2020 ; Wu et al 2021 ; Chu et al 2021 ). Thapa et al attempted to knock out the mdh gene encoding malate dehydrogenase to inhibit succinate production and further enhance 2,3-BDO production and then showed that 2,3-BDO was not significantly enhanced (Thapa et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, less research has been done in recent years to limit the succinate production (Thapa et al 2019 ). Instead, most studies have focused on limiting lactate (Ge et al 2020 ; Wu et al 2021 ; Chu et al 2021 ). Thapa et al attempted to knock out the mdh gene encoding malate dehydrogenase to inhibit succinate production and further enhance 2,3-BDO production and then showed that 2,3-BDO was not significantly enhanced (Thapa et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A dynamic tolerance engineering strategy was designed by introducing the deinococcal response regulator DR1558 to improve microbial productivity and relieve metabolic burden. Engineering strategies to improve cellular stress resistance such as adaptive evolution (Huang et al 2023 ; Zhou et al 2023 ), regulatory factor introduction (Wu et al 2021 ), tolerance target screening (Li et al 2023 ; Cámara et al 2022 ), and transport engineering (Mutanda et al 2022 ) are now widely developed. Among them, the introduction of regulatory factors is a useful strategy to improve tolerance to target compounds even in the face of unknown toxicity mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wu et al (33) knocked out the NADH dehydrogenase genes (nuoC/nuoD) to increase NADH pool and knocked out the lactate dehydrogenase (ldh) to reduce other consumption of NADH, their results showed that 2,3-butanediol production increased by 67% and 71.2%, respectively.…”
Section: Strategy For Malate Accumulationmentioning
confidence: 99%